Meaning of sustainable development in innovation management in enterprises - Iwona Kłosok-Bazan; Joanna Machnik-Słomka (Economic and Environmental Studies (E&ES), 2017)
According to the Europe 2020 Strategy, the European's countries development should be based on three interrelated priorities: smart, sustainable and inclusive growth. All this priorities should be based on the increasing role of knowledge and innovation as the driving forces of future sustainable growth. The aim of this article is not to consider these categories separately, but their combination which allowed to present the possibilities and advantages for enterprises, resulting from the innovative activity directed at the sustainable development, using the sustainable management and sustainable production.
Keywords: Q1; Q5; L23; L31; O31; 330; sustainable development; innovation management; sustainable management